Аналіз ключових факторів айдентики - Федосенко, Я. С. (ХНУРЕ, 2025)
The work is devoted to the study of identity as a complex system of visual, verbal and symbolic elements that form a recognizable image. Theoretical approaches to understanding identity, its role in brand positioning, psychological impact on the audience and significance in the socio-cultural context are considered. Identity is considered as a key factor of success in the modern world. Its components and significance in various spheres, from business to culture, are analyzed.
Keywords: айдентика